Hollow nano aggregate microsphere catalyst, preparation method and application thereof
The hollow nano-agglomerate microsphere catalyst prepared by spray drying technology solves the problem of difficult separation and recovery of existing catalysts during the polyester degradation process, and achieves the effect of efficiently degrading polyester and simplifying catalyst recovery.
Patent Information
- Application Number
- CN202310268525.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-15
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-03-15
AI Technical Summary
Existing catalysts are difficult to efficiently separate and recover during the recovery process of degraded polyester, and the catalytic activity is insufficient, resulting in low degradation efficiency and high energy consumption of polyester.
A hollow nano-aggregated microsphere catalyst is prepared by spray drying technology. The catalyst consists of active nanoparticles, has a hollow structure inside, has a controlled size and morphology, and can contain magnetic nanoparticles for magnetic separation.
The complete degradation of polyester in a short time under mild conditions is achieved, which significantly improves the reaction efficiency, reduces energy consumption, and simplifies the catalyst recovery process, achieving a monomer product yield of more than 90%.
Smart Images

Figure CN116237052B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyester recycling; more specifically, to a hollow nano aggregate microsphere catalyst, a preparation method and application thereof in recycling of degraded polyester. Background Art
[0002] Polyester plastic mainly refers to polyethylene terephthalate (PET), which is a petroleum-based plastic synthesized by esterification of terephthalic acid and ethylene glycol to form ethylene terephthalate, and then condensed by monomers. Because it is non-toxic and odorless, has high transparency, excellent mechanical properties, and chemical resistance stability, it is widely used in various fields such as food storage, lightweight vehicle construction, and building insulation. Among them, less than 10% of PET plastics are recycled, and 40% are disposable products with extremely short service life. It is difficult to degrade in a short time and usually goes through a one-way process of "production-waste-treatment". Plastic waste produces at least 5-10 times the mass of carbon emissions when landfilled or incinerated. When leaked into the natural environment, it seriously affects the marine and terrestrial ecology, and may even be ingested by humans in the form of microplastics. Therefore, plastic recycling and regeneration technology aimed at material recovery has received widespread attention.
[0003] The current recycling method for waste plastics is usually physical recycling, which is to simply wash the polymer, then melt it and reshape it. However, compared with the original plastic, these recycled plastics not only have poorer performance, but also lower value, which is not enough to make up for the cost of recycling, sorting and processing. Chemical recycling methods can depolymerize certain plastics into monomers, and the resulting monomers can be converted into high-value chemicals, or repolymerized into polyesters with the original physical and chemical properties. However, this process has high reaction temperatures and pressures, and requires the use of efficient catalysts to reduce reaction energy consumption and simplify separation and recovery routes.
[0004] The selection of catalysts is a difficulty in current research. It has been reported that homogeneous catalysts used to degrade polyester, such as metal (Zn, Co, Mn, etc.) acetates, ionic liquids, etc., are not easy to separate from the product and reuse. In order to improve the degradation efficiency, nanoscale and highly dispersed metal particles and metal oxide particles, and graphite carbon nitride are also used to degrade polyester. For example, Du et al. used pseudo-homogeneous ZnO nanodispersion for ethylene glycol degradation of PET, which can depolymerize PET at a degradation rate of 82% within 1 hour at 180°C (Du JT, Sun Q, Zeng XF, et al. ZnO nanodispersion as pseudohomogeneous catalyst for alcoholysis of polyethylene terephthalate [J]. Chemical Engineering Science, 2020, 220: 115642.). Although the degradation performance is good, it is also difficult to completely separate this type of catalyst from the product, and the residual ultra-small nanoparticles can easily reduce the quality of the product.
[0005] In order to solve the problem of catalyst separation and recovery, researchers have introduced magnetic heterogeneous glycolysis catalysts through various methods, including doping magnetite, synthesizing cobalt ferrite or zinc ferrite, coating nano oxides or boron nitride on magnetic nanoparticles, etc. For example, Li et al. used zinc ferrite nanoparticles to degrade PET plastic at 197°C, with a PET degradation rate of 100% within 2 hours and a monomer yield of 79.82% (Li Y, Li K, Li M, et al. Zinc-doped ferrite nanoparticles as magnetic recyclable catalysts for scale-up glycolysis of poly (ethylene terephthalate) wastes [J]. Advanced Powder Technology, 2022, 33 (3): 103444.). However, their catalytic activity is far inferior to that of the above-mentioned pseudo-homogeneous catalysts.
[0006] Therefore, providing a catalyst that is efficient, easy to separate, and can be used for large-scale industrial production is of great significance for reducing the energy consumption of polyester recovery and simplifying the catalyst recovery process. Summary of the invention
[0007] The first technical problem to be solved by the present invention is to provide a hollow nano aggregate microsphere catalyst.
[0008] The second technical problem to be solved by the present invention is to provide a method for preparing a hollow nano aggregate microsphere catalyst. The method has no solvent residue, is widely applicable to nano dispersions or suspensions, and is suitable for large-scale preparation and production. By controlling the size and dispersibility of pre-synthesized nanoparticles and assembling them through spray drying, hollow nano aggregate microspheres with controllable size and morphology can be obtained.
[0009] The third technical problem to be solved by the present invention is to provide an application of a hollow nano aggregate microsphere catalyst in the recycling of degraded polyester.
[0010] In order to solve the above-mentioned first technical problem, the present invention adopts the following technical solution:
[0011] A hollow nano aggregate microsphere catalyst, the surface of the catalyst is composed of active nanoparticles, and the interior is a hollow structure; the active nanoparticles are dispersed in a solvent to form a dispersion or a suspension, and then combined into active hollow nano aggregate microspheres by spray drying; the particle size of the active nanoparticles is 2-100nm; the particle size of the hollow nano aggregate microspheres is 1-30μm.
[0012] Preferably, the hollow nano-aggregate microsphere catalyst further comprises magnetic nano-particles; the magnetic nano-particles and active nano-particles are dispersed in a solvent to form a dispersion or suspension, and then combined into a composite magnetic hollow nano-aggregate microsphere catalyst by spray drying.
[0013] Preferably, the active nanoparticles are selected from one or more of TiO2, CeO2, MnO2, MoO3, CuO, Cu2O, ZnO, MgO, NiO, ZrO2, Al2O3, CdO, Sb2O3, V2O5, SiO2 dispersions or suspensions.
[0014] Preferably, the magnetic nanoparticles are selected from one or more of γ-Fe2O3, Fe3O4, FeO, FeCo, CoFe2O4, ZnFe2O4, NiFe2O4, MnFe2O4, Co3O4, Mn3O4, FeN, and Fe2N.
[0015] To solve the above second technical problem, the present invention adopts the following technical solution:
[0016] A method for preparing a hollow nano aggregate microsphere catalyst comprises the following steps:
[0017] S11, dispersing the active nanoparticles in a solvent and uniformly mixing them to form a dispersion or a suspension;
[0018] S12, pumping the above dispersion or suspension into a spray dryer for spray drying to obtain active hollow nano aggregate microspheres.
[0019] Preferably, in step S11, the active nanomaterial is one or more selected from TiO2, CeO2, MnO2, MoO3, CuO, Cu2O, ZnO, MgO, NiO, ZrO2, Al2O3, CdO, Sb2O3, V2O5, SiO2 dispersions or suspensions.
[0020] Preferably, in step S11, the solvent is one or more of water, methanol, ethanol, ethylene glycol, cyclohexane, tetrahydrofuran, toluene, acetone, and N,N'-diethylformamide.
[0021] Preferably, in step S11, the solid content of the dispersion or suspension is 0.1-10%; more preferably, the solid content of the dispersion or suspension is 1-5%.
[0022] Preferably, in step S12, the inlet temperature of the spray drying is 90-180°C; more preferably, the inlet temperature of the spray drying is 110-140°C.
[0023] Preferably, in step S12, the input speed of the dispersion or suspension is 0.1-2 L / h; more preferably, the input speed of the dispersion or suspension is 0.3-1 L / h.
[0024] Preferably, in step S12, the compressed air velocity during spray drying is 400-800 L / h; more preferably, the compressed air velocity during spray drying is 500-700 L / h.
[0025] A method for preparing composite magnetic hollow nano aggregate microspheres comprises the following steps:
[0026] S21, dispersing the active nanoparticles and the magnetic nanoparticles in a solvent, and mixing them uniformly to obtain a mixed dispersion or suspension;
[0027] S22, pumping the mixed dispersion or suspension into a spray dryer for spray drying to obtain composite magnetic hollow nano aggregate microspheres.
[0028] Preferably, in step S21, the active nanoparticles are selected from one or more of TiO2, CeO2, MnO2, MoO3, CuO, Cu2O, ZnO, MgO, NiO, ZrO2, Al2O3, CdO, Sb2O3, V2O5, and SiO2.
[0029] Preferably, in step S21, the magnetic nanoparticles are selected from one or more of γ-Fe2O3, Fe3O4, FeO, FeCo, CoFe2O4, ZnFe2O4, NiFe2O4, MnFe2O4, Co3O4, Mn3O4, FeN, and Fe2N.
[0030] Preferably, in step S21, the mass ratio of the active nanoparticles to the magnetic nanoparticles is 0.1-10:1.
[0031] Preferably, in step S21, the solvent is selected from one or more of water, methanol, ethanol, ethylene glycol, cyclohexane, tetrahydrofuran, toluene, acetone, and N,N'-diethylformamide.
[0032] Preferably, in step S21, the solid content of the mixed dispersion or suspension is 0.1-10%; more preferably, the solid content of the mixed dispersion or suspension is 1-5%;
[0033] Preferably, in step S22, the inlet temperature of the spray drying is 90-180°C; more preferably, the inlet temperature of the spray drying is 110-140°C;
[0034] Preferably, in step S22, the input speed of the mixed dispersion or suspension is 0.1-2 L / h; more preferably, the input speed of the mixed dispersion or suspension is 0.3-1 L / h;
[0035] Preferably, in step S22, the compressed air velocity during spray drying is 400-800 L / h; more preferably, the compressed air velocity during spray drying is 500-700 L / h.
[0036] To solve the third technical problem, the present invention adopts the following technical solution:
[0037] An application of a hollow nano aggregate microsphere catalyst in the recycling of degraded polyester comprises the following steps:
[0038] S31, adding polyester fragments, alcoholysis agent and active hollow nano aggregate microsphere catalyst into a reaction kettle, stirring at a reaction temperature, so that the polyester undergoes a catalytic degradation reaction;
[0039] S32, centrifugally separating the active hollow nano aggregate microsphere catalyst while hot, and dissolving and filtering to obtain the purified product after the system is cooled.
[0040] Preferably, in step S31, the polyester fragments are one or more of polyethylene terephthalate, polybutylene terephthalate, polycarbonate, polycaprolactone, polylactide, and polyurethane.
[0041] Preferably, in step S31, the alcoholysis agent is one or more of methanol, ethanol, ethylene glycol, diethylene glycol, isooctyl alcohol, propylene glycol, butanediol, hexanediol, and sec-butanol.
[0042] Preferably, in step S31, the mass ratio of the polyester fragments, the alcoholysis agent and the active hollow nano-aggregate microsphere catalyst is 1:3-20:0.005-0.05; more preferably, the mass ratio is 1:5-10:0.005-0.02.
[0043] Preferably, in step S31, the reaction temperature is 160-210°C, and the degradation reaction time is 10-120 min; more preferably, the reaction temperature is 170-197°C.
[0044] Preferably, in step S31, the stirring rate is 100-1000 r / min; more preferably, the stirring rate is 400-700 r / min.
[0045] An application of a composite magnetic hollow nano aggregate microsphere catalyst in the recycling of degraded polyester comprises the following steps:
[0046] S41, adding polyester fragments, alcoholysis agent and composite magnetic hollow nano aggregate microsphere catalyst into a reaction kettle, stirring at a reaction temperature, so that the polyester undergoes a catalytic degradation reaction;
[0047] S42, while hot, use an external magnetic field to separate the composite magnetic hollow nano aggregate microsphere catalyst, and after the system is cooled, dissolve and filter to obtain the purified product.
[0048] Preferably, in step S41, the polyester fragments are one or more of polyethylene terephthalate, polybutylene terephthalate, polycarbonate, polycaprolactone, polylactide, and polyurethane.
[0049] Preferably, in step S41, the alcoholysis agent is one or more of methanol, ethanol, ethylene glycol, diethylene glycol, isooctyl alcohol, propylene glycol, butanediol, hexanediol, and sec-butanol.
[0050] Preferably, in step S41, the mass ratio of the polyester fragments, the alcoholysis agent and the composite magnetic hollow nano-aggregate microsphere catalyst is 1:3-20:0.005-0.05; more preferably, the mass ratio is 1:5-10:0.005-0.02.
[0051] Preferably, in step S41, the reaction temperature is 160-210°C, and the reaction time is 10-120 min; more preferably, the reaction temperature is 180-200°C;
[0052] Preferably, in step S41, the stirring rate is 100-1000 r / min; more preferably, the stirring rate is 400-700 r / min.
[0053] Any range described in the present invention includes the end value and any numerical value between the end values and any sub-range formed by the end value or any numerical value between the end values.
[0054] Unless otherwise specified, all raw materials in the present invention can be purchased from the market, and the equipment used in the present invention can adopt conventional equipment in the relevant field or refer to the existing technology in the relevant field.
[0055] Compared with the prior art, the present invention has the following beneficial effects: :
[0056] 1) The present invention synthesizes a hollow nano aggregate microsphere catalyst for degrading polyester by spray drying. The preparation method has no solvent residue, has a wide range of applications for nano dispersions or suspensions, and is suitable for large-scale preparation and production. By controlling the size and dispersibility of pre-synthesized nanoparticles, hollow nano aggregate microspheres with controllable size and morphology can be obtained through spray drying assembly.
[0057] 2) The active hollow nano-aggregate microsphere catalyst can completely degrade polyester in a short time under relatively mild conditions, significantly improve the reaction efficiency, and reduce the demand for high-temperature and high-pressure equipment for polyester depolymerization reactions. It can completely degrade polyester under the conditions of a reaction temperature of 170-197°C and a reaction time of 10-120 minutes, and achieve a monomer product yield of more than 90%.
[0058] 3) The composite magnetic hollow nano-aggregate microsphere catalyst can completely degrade polyester in a short time under relatively mild conditions. The synergistic effect between the active nanoparticles on the surface of the hollow structure and the magnetic nanoparticles enhances the catalyst performance and improves the degradation effect of the corresponding nanoparticles. Under the conditions of a reaction temperature of 180-200°C and a reaction time of 10-120 minutes, polyester can be completely degraded and a monomer product yield of more than 90% can be achieved.
[0059] 4) The present invention can realize simple and rapid recovery of polyester degradation catalysts by centrifugal separation of the catalysts or rapid magnetic separation of the catalysts by external magnetic field. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] The specific embodiments of the present invention will be further described in detail below with reference to the accompanying drawings.
[0061] Figure 1 is a transmission electron microscope photograph of magnetic nanoparticles in the dispersion or suspension used to prepare hollow nanoaggregate microspheres in Example 1;
[0062] Figure 2is a transmission electron microscope photograph of active nanoparticles in the dispersion or suspension used to prepare hollow nanoaggregate microspheres in Example 1;
[0063] Figure 3 is a scanning electron microscope photograph of the hollow nano aggregate microspheres in Example 1;
[0064] Figure 4 This is a scanning electron microscope photograph of the hollow nano-aggregate microspheres in Example 1 after being cracked by ultrasound for 10 minutes;
[0065] Figure 5 is the hysteresis loop of the hollow nano-aggregate microspheres in Example 1;
[0066] Figure 6 is the XRD pattern of the hollow nano aggregate microspheres in Example 1;
[0067] Figure 7 This is a physical picture of the hollow nano-aggregate microspheres in Example 1 being attracted and separated by an external magnetic field after catalytic degradation of polyester;
[0068] Figure 8 is the nuclear magnetic resonance spectrum of the product obtained by degrading polyester in Example 1;
[0069] Fig. 9 is a scanning electron microscope photograph of the hollow nano aggregate microspheres in Example 2;
[0070] Fig.10 is a scanning electron microscope photograph of the hollow nano aggregate microspheres in Example 3;
[0071] Fig.11 This is a scanning electron microscope photograph of the hollow nanoaggregate microspheres in Example 4. DETAILED DESCRIPTION
[0072] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0073] As one aspect of the present invention, the present invention provides a hollow nano aggregate microsphere catalyst, the surface of the catalyst is composed of active nanoparticles, and the interior is a hollow structure; the active nanoparticles are dispersed in a solvent to form a dispersion or suspension, and then combined into active hollow nano aggregate microspheres by spray drying; the particle size of the active nanoparticles is 2-100nm; the particle size of the hollow nano aggregate microspheres is 1-30μm.
[0074] In certain embodiments, the hollow nano-aggregate microsphere catalyst further includes magnetic nanoparticles; the magnetic nanoparticles and active nanoparticles are dispersed in a solvent to form a dispersion or suspension, and then combined into composite magnetic hollow nano-aggregate microspheres by spray drying.
[0075] In certain embodiments, the active nanoparticles are selected from one or more of TiO2, CeO2, MnO2, MoO3, CuO, Cu2O, ZnO, MgO, NiO, ZrO2, Al2O3, CdO, Sb2O3, V2O5, and SiO2 dispersions or suspensions.
[0076] In certain embodiments, the magnetic nanoparticles are selected from one or more of γ-Fe2O3, Fe3O4, FeO, FeCo, CoFe2O4, ZnFe2O4, NiFe2O4, MnFe2O4, Co3O4, Mn3O4, FeN, and Fe2N.
[0077] As another aspect of the present invention, a method for preparing a hollow nano aggregate microsphere catalyst comprises the following steps:
[0078] S11, dispersing the active nanoparticles in a solvent and uniformly mixing them to form a dispersion or a suspension;
[0079] S12, pumping the above dispersion or suspension into a spray dryer for spray drying to obtain active hollow nano aggregate microspheres.
[0080] In certain embodiments, in step S11, the active nanomaterial is one or more selected from TiO2, CeO2, MnO2, MoO3, CuO, Cu2O, ZnO, MgO, NiO, ZrO2, Al2O3, CdO, Sb2O3, V2O5, and SiO2 dispersions or suspensions.
[0081] In certain embodiments, in step S11, the solvent is one or more of water, methanol, ethanol, ethylene glycol, cyclohexane, tetrahydrofuran, toluene, acetone, and N,N'-diethylformamide.
[0082] In certain embodiments, in step S11, the solid content of the dispersion or suspension is 0.1-10%; more preferably, the solid content of the dispersion or suspension is 1-5%.
[0083] In certain embodiments, in step S12, the inlet temperature of the spray drying is 90-180°C; more preferably, the inlet temperature of the spray drying is 110-140°C.
[0084] In certain embodiments, in step S12, the input rate of the dispersion or suspension is 0.1-2 L / h; more preferably, the input rate of the dispersion or suspension is 0.3-1 L / h.
[0085] In certain embodiments, in step S12, the compressed air velocity during spray drying is 400-800 L / h; more preferably, the compressed air velocity during spray drying is 500-700 L / h.
[0086] As another aspect of the present invention, a method for preparing composite magnetic hollow nano aggregate microspheres of the present invention comprises the following steps:
[0087] S21, dispersing the active nanoparticles and the magnetic nanoparticles in a solvent, and mixing them uniformly to obtain a mixed dispersion or suspension;
[0088] S22, pumping the mixed dispersion or suspension into a spray dryer for spray drying to obtain composite magnetic hollow nano aggregate microspheres.
[0089] In certain embodiments, in step S21, the active nanoparticles are selected from one or more of TiO2, CeO2, MnO2, MoO3, CuO, Cu2O, ZnO, MgO, NiO, ZrO2, Al2O3, CdO, Sb2O3, V2O5, and SiO2.
[0090] In certain embodiments, in step S21, the magnetic nanoparticles are selected from one or more of γ-Fe2O3, Fe3O4, FeO, FeCo, CoFe2O4, ZnFe2O4, NiFe2O4, MnFe2O4, Co3O4, Mn3O4, FeN, and Fe2N.
[0091] In certain embodiments, in step S21, the mass ratio of the active nanoparticles to the magnetic nanoparticles is 0.1-10:1.
[0092] In certain embodiments, in step S21, the solvent is selected from one or more of water, methanol, ethanol, ethylene glycol, cyclohexane, tetrahydrofuran, toluene, acetone, and N,N'-diethylformamide.
[0093] In some embodiments, in step S21, the solid content of the mixed dispersion or suspension is 0.1-10%; more preferably, the solid content of the mixed dispersion or suspension is 1-5%;
[0094] In certain embodiments, in step S22, the spray drying inlet temperature is 90-180°C; more preferably, the spray drying inlet temperature is 110-140°C;
[0095] In some embodiments, in step S22, the input speed of the mixed dispersion or suspension is 0.1-2 L / h; more preferably, the input speed of the mixed dispersion or suspension is 0.3-1 L / h;
[0096] In certain embodiments, in step S22, the compressed air velocity during spray drying is 400-800 L / h; more preferably, the compressed air velocity during spray drying is 500-700 L / h.
[0097] As another aspect of the present invention, the application of a hollow nano aggregate microsphere catalyst in the recycling of degraded polyester comprises the following steps:
[0098] S31, adding polyester fragments, alcoholysis agent and active hollow nano aggregate microsphere catalyst into a reaction kettle, stirring at a reaction temperature, so that the polyester undergoes a catalytic degradation reaction;
[0099] S32, centrifugally separating the active hollow nano aggregate microsphere catalyst while hot, and dissolving and filtering to obtain the purified product after the system is cooled.
[0100] In certain embodiments, in step S31, the polyester fragments are one or more of polyethylene terephthalate, polybutylene terephthalate, polycarbonate, polycaprolactone, polylactide, and polyurethane.
[0101] In certain embodiments, in step S31, the alcoholysis agent is one or more of methanol, ethanol, ethylene glycol, diethylene glycol, isooctyl alcohol, propylene glycol, butanediol, hexanediol, and sec-butanol.
[0102] In certain embodiments, in step S31, the mass ratio of the polyester fragments, the alcoholysis agent and the active hollow nano-aggregate microsphere catalyst is 1:3-20:0.005-0.05; more preferably, the mass ratio is 1:5-10:0.005-0.02.
[0103] In certain embodiments, in step S31, the reaction temperature is 160-210°C, and the degradation reaction time is 10-120 min; more preferably, the reaction temperature is 170-197°C.
[0104] In certain embodiments, in step S31, the stirring rate is 100-1000 r / min; more preferably, the stirring rate is 400-700 r / min.
[0105] As another aspect of the present invention, the application of a composite magnetic hollow nano aggregate microsphere catalyst in the recycling of degraded polyester comprises the following steps:
[0106] S41, adding polyester fragments, alcoholysis agent and composite magnetic hollow nano aggregate microsphere catalyst into a reaction kettle, stirring at a reaction temperature, so that the polyester undergoes a catalytic degradation reaction;
[0107] S42, while hot, use an external magnetic field to separate the composite magnetic hollow nano aggregate microsphere catalyst, and after the system is cooled, dissolve and filter to obtain the purified product.
[0108] In certain embodiments, in step S41, the polyester fragments are one or more of polyethylene terephthalate, polybutylene terephthalate, polycarbonate, polycaprolactone, polylactide, and polyurethane.
[0109] In certain embodiments, in step S41, the alcoholysis agent is one or more of methanol, ethanol, ethylene glycol, diethylene glycol, isooctyl alcohol, propylene glycol, butanediol, hexanediol, and sec-butanol.
[0110] In certain embodiments, in step S41, the mass ratio of the polyester fragments, the alcoholysis agent and the composite magnetic hollow nano-aggregate microsphere catalyst is 1:3-20:0.005-0.05; more preferably, the mass ratio is 1:5-10:0.005-0.02.
[0111] In certain embodiments, in step S41, the reaction temperature is 160-210° C., and the reaction time is 10-120 min, including but not limited to 20-120 min, 30-120 min, 40-120 min, 50-120 min, 60-120 min, 70-120 min, 80-120 min, 90-120 min, 100-120 min, 20-100 min, 30-100 min, 40- 100min, 50-100min, 60-100min, 70-100min, 80-100min, 90-100min, 20-80min, 30-80min, 40-80min, 50-80min, 60-80min, 70-80min, 20-60min, 30-60min, 40-60min, or 50-60min; more preferably, the reaction temperature is 180-200°C;
[0112] In certain embodiments, in step S41, the stirring rate is 100-1000 r / min; more preferably, the stirring rate is 400-700 r / min.
[0113] Example 1
[0114] A preparation method and application of CeO2-Fe3O4 composite magnetic hollow nano aggregate microsphere catalyst,
[0115] In this embodiment, aqueous Fe3O4 dispersion with an average particle size of 10 nm and aqueous CeO2 dispersion with an average particle size of 3 nm are used as raw materials, and CeO2-Fe3O4 composite magnetic hollow nano-aggregate microspheres are prepared by spray drying, and used to degrade PET polyester, comprising the following steps:
[0116] (1) mixing a CeO2 aqueous dispersion having a solid content of 2% and a Fe3O4 aqueous dispersion having a solid content of 2% in a ratio of CeO2 nanoparticles to Fe3O4 nanoparticles of 2:1 by mass;
[0117] (2) The spray drying inlet temperature is 120° C., the feed flow rate is 0.5 L / h, and the compressed gas flow rate is 600 L / h. After the inlet temperature is stabilized at the set value, the mixed dispersion is pumped into the spray dryer for spray drying, and the obtained CeO2-Fe3O4 composite magnetic hollow nano-aggregate microsphere catalyst is taken out from the collection chamber;
[0118] (3) 10 g of PET powder, 60 g of ethylene glycol solvent, and 0.1 g of CeO2-Fe3O4 catalyst were added into a parallel high-pressure reactor and reacted at 180°C for 40 min under magnetic stirring at 500 r / min;
[0119] (4) While the catalyst is hot, a square magnet is used to attract it. After the system is cooled, the monomer product is obtained by dissolving and filtering.
[0120] After the reaction, the PET degradation rate was measured to be 54.5%, and the monomer product yield was 50.3%.
[0121] Figure 1 This is a transmission photograph of the aqueous Fe3O4 dispersion used in Example 1, with an average particle size of about 10 nm.
[0122] Figure 2 This is a transmission photograph of the aqueous CeO2 dispersion used in Example 1, with an average particle size of about 3 nm.
[0123] Figure 3 This is a scanning electron microscope photograph of the CeO2-Fe3O4 composite magnetic hollow nano-aggregate microspheres in Example 1. It can be seen that the average particle size of the aggregates is 1-10 μm, the morphology is a regular sphere, the surface is smooth and full, and the particles are closely arranged.
[0124] Figure 4 This is a scanning electron microscope photograph of the composite magnetic hollow nano-aggregate microspheres in Example 1 after the spheres are cracked by ultrasound for 10 minutes. It can be seen that the interior of the hollow nano-aggregate microspheres is a hollow structure.
[0125] Figure 5This is the hysteresis loop of the CeO2-Fe3O4 composite magnetic hollow nano-aggregate microspheres in Example 1, with a magnetic property of 22.5emu / g.
[0126] Figure 6 This is the XRD diagram of the CeO2-Fe3O4 composite magnetic hollow nanoaggregate microspheres in Example 1.
[0127] Figure 7 This is a physical picture of the CeO2-Fe3O4 composite magnetic hollow nano-aggregate microspheres in Example 1 being attracted and separated by an external magnetic field after catalyzing the degradation of polyester. It can be seen that the catalyst is obviously separated by magnetism.
[0128] Figure 8 This is the carbon nuclear magnetic resonance spectrum of the product obtained by degrading polyester in Example 1. It can be seen that the main component of the degradation product is ethylene terephthalate.
[0129] Example 2
[0130] A preparation method and application of ZnO-Fe3O4 composite magnetic hollow nano aggregate microsphere catalyst,
[0131] In this embodiment, a ZnO-Fe3O4 composite magnetic hollow nano-aggregate microsphere catalyst is prepared by spray drying using an aqueous Fe3O4 dispersion with an average particle size of 10 nm and an aqueous ZnO dispersion with an average particle size of 6 nm as raw materials, and the catalyst is used to degrade PET polyester, comprising the following steps:
[0132] (1) mixing a ZnO aqueous dispersion having a solid content of 2% and a Fe3O4 aqueous dispersion having a solid content of 2% in a ratio of 2:1 between the mass ratio of ZnO nanoparticles and the mass ratio of Fe3O4 nanoparticles;
[0133] (2) The spray drying inlet temperature is 120° C., the feed flow rate is 0.5 L / h, and the compressed gas flow rate is 600 L / h. After the inlet temperature is stabilized at the set value, the mixed dispersion is pumped into the spray dryer for spray drying, and the obtained ZnO-Fe3O4 composite magnetic hollow nano-aggregate microsphere catalyst is taken out from the collection chamber;
[0134] (3) 10 g PET powder, 60 g ethylene glycol solvent, and 0.1 g ZnO-Fe3O4 catalyst were added into a parallel high-pressure reactor and reacted at 180°C for 40 min under magnetic stirring at 500 r / min;
[0135] (4) While the catalyst is hot, a square magnet is used to attract it. After the system is cooled, the monomer product is obtained by dissolving and filtering.
[0136] After the reaction, the degradation rate of PET was measured to be 72.2%, and the yield of the monomer product was 68.3%.
[0137] Fig. 9 This is a scanning electron microscope photograph of the composite magnetic hollow nano aggregate microspheres in Example 2. It can be seen that the average particle size of the aggregates is 1-10 μm, the morphology is a regular sphere, the surface is smooth and full, and the particles are closely arranged.
[0138] Example 3
[0139] A preparation method and application of CeO2 active hollow nano aggregate microsphere catalyst,
[0140] In this embodiment, CeO2 active hollow nano aggregate microspheres are prepared by spray drying using an aqueous CeO2 dispersion with an average particle size of 3 nm as a raw material, and are used to degrade PET polyester, comprising the following steps:
[0141] (1) preparing an aqueous CeO2 dispersion with a solid content of 2%;
[0142] (2) The spray drying inlet temperature is 120°C, the feed flow rate is 0.35 L / h, and the compressed gas flow rate is 700 L / h. After the inlet temperature is stabilized at the set value, the above dispersion is pumped into the spray dryer for spray drying, and the obtained CeO2 active hollow nano-aggregate microsphere catalyst is taken out from the collection chamber;
[0143] (3) 10 g PET powder, 60 g ethylene glycol solvent, and 0.1 g CeO2 active hollow nanoaggregate microsphere catalyst were added into a parallel high-pressure reactor and reacted at 180 °C, 40 min, and 500 r / min magnetic stirring;
[0144] (4) Centrifugally separate the catalyst while hot, and after the system is cooled, dissolve and filter to obtain the monomer product.
[0145] After the reaction, the degradation rate of PET was measured to be 74.2%, and the yield of the monomer product was 70.1%.
[0146] Fig.10 This is a scanning electron microscope photograph of the active hollow nano aggregate microspheres in Example 4. It can be seen that the average particle size of the aggregates is 1-10 μm, the morphology is regular, the surface is smooth and full, and the particles are closely arranged.
[0147] Example 4
[0148] A preparation method and application of ZnO active hollow nano aggregate microsphere catalyst,
[0149] In this embodiment, ZnO active hollow nano aggregate microspheres are prepared by spray drying using an aqueous ZnO dispersion with an average particle size of 6 nm as a raw material, and the microspheres are used to degrade PET polyester, including the following steps:
[0150] (1) preparing an aqueous ZnO dispersion with a solid content of 2%;
[0151] (2) The spray drying inlet temperature is 120° C., the feed flow rate is 0.5 L / h, and the compressed gas flow rate is 600 L / h. After the inlet temperature is stabilized at the set value, the above dispersion is pumped into the spray dryer for spray drying, and the obtained ZnO active hollow nano-aggregate microsphere catalyst is taken out from the collection chamber;
[0152] (3) 10 g of PET powder, 60 g of ethylene glycol solvent, and 0.1 g of ZnO active hollow nanoaggregate microsphere catalyst were added into a parallel high-pressure reactor and reacted at 180 ° C, 40 min, and 500 r / min magnetic stirring;
[0153] (4) Centrifugally separate the catalyst while hot, and after the system is cooled, dissolve and filter to obtain the monomer product.
[0154] After the reaction, the degradation rate of PET was measured to be 81.0%, and the yield of the monomer product was 78.9%.
[0155] Fig.11 This is a scanning electron microscope photograph of the active hollow nano aggregate microspheres in Example 3. It can be seen that the average particle size of the aggregates is 1-10 μm, the morphology is a regular sphere, the surface is smooth and full, and the particles are closely arranged.
[0156] Example 5
[0157] Example 2 was repeated, except that the polyester degradation temperature in step (3) was changed to 160-200° C. and the degradation time was 40 min. After the reaction, the PET degradation rate and monomer product yield were measured as shown in Table 1.
[0158] Table 1
[0159] Reaction temperature (℃) PET degradation rate (%) Monomer yield (%) 160 18.4 16.5 170 37.9 35.5 180 72.2 68.3 190 100.0 95.4 200 100.0 94.5
[0160] Example 6
[0161] Example 2 was repeated, except that the polyester degradation time in step (3) was changed to 10-60 min, the degradation temperature was 180° C., and the PET degradation rate and monomer product yield were measured after the reaction as shown in Table 2.
[0162] Table 2
[0163] Reaction time (min) PET degradation rate (%) Monomer yield (%) 10 26.0 24.5 20 43.1 40.4 30 61.7 56.8 40 72.2 68.3 50 81.4 77.5 60 93.8 90.2
[0164] Example 7
[0165] Example 2 was repeated, except that the temperature of 180° C. for 40 min in step (3) was changed to 190° C. for 40 min, and the magnetic catalyst collected in step (4) was washed with ethanol and then used in a subsequent catalyst recycling experiment. The PET degradation rate and monomer product yield after the reaction were measured as shown in Table 3.
[0166] Table 3
[0167] Reaction cycle (number) PET degradation rate (%) Monomer yield (%) 1 100 95.4 2 100 92.6 3 98.3 91.5 4 93.6 89.2 5 90.1 87.2
[0168] Example 8
[0169] Example 2 was repeated, except that the polyester degradation condition in step (3) was changed to a reaction without stirring. After the reaction, the PET degradation rate was measured to be 1.7%.
[0170] Example 9
[0171] Example 2 was repeated, except that the catalyst added in step (3) was changed to 0.05 g ZnO-Fe3O4. After the reaction, the PET degradation rate was measured to be 60.9%, and the monomer product yield was 54.5%.
[0172] Example 10
[0173] Example 2 was repeated, except that the reaction solvent in step (3) was changed to 60 g of sec-butanol solvent. After the reaction, the PET degradation rate was measured to be 1.6%.
[0174] Embodiment 11
[0175] Example 2 was repeated, except that the polyester to be degraded in step (3) was replaced by polycarbonate (PC) powder, and the PC degradation rate was measured to be 100% after the reaction.
[0176] Comparative Example 1
[0177] In this comparative example, an aqueous CeO2 dispersion with an average particle size of 3 nm and an aqueous Fe3O4 dispersion with an average particle size of 10 nm are used as catalysts, and they are used to degrade PET polyester in the same proportion as in Example 1, comprising the following steps:
[0178] (1) 10 g PET powder, 60 g ethylene glycol solvent, 0.067 g CeO2 and 0.033 g Fe3O4 catalyst were added into a parallel high-pressure reactor and reacted at 180°C for 40 min under 500 r / min magnetic stirring;
[0179] (2) After the system is cooled, the monomer product is obtained by dissolving and filtering.
[0180] After the reaction, the degradation rate of PET was measured to be 40.5%, and the yield of monomer product was 36.4%, which was about 15% lower than that of hollow nano aggregate microspheres.
[0181] It can be seen that the CeO2 and Fe3O4 nanoparticles directly mixed in the same proportion do not have the synergistic effect between the active nanoparticles and the magnetic nanoparticles in the CeO2-Fe3O4 hollow nanoaggregate microsphere catalyst constructed by spray drying, and the catalytic efficiency cannot be improved. In addition, the CeO2 nanoparticles cannot be recovered by an external magnetic field.
[0182] Comparative Example 2
[0183] In this comparative example, an aqueous ZnO dispersion having an average particle size of 6 nm and an aqueous Fe3O4 dispersion having an average particle size of 10 nm are used as catalysts, and the catalysts are used to degrade PET polyester in the same proportion as in Example 2, comprising the following steps:
[0184] (1) 10 g PET powder, 60 g ethylene glycol solvent, 0.067 g ZnO and 0.033 g Fe3O4 catalyst were added into a parallel high-pressure reactor and reacted at 180°C for 40 min under magnetic stirring at 500 r / min;
[0185] (2) After the system is cooled, the monomer product is obtained by dissolving and filtering.
[0186] After the reaction, the PET degradation rate was measured to be 51.5%, and the monomer product yield was 48.4%, which was about 20% lower than that of the hollow nano-aggregate microspheres.
[0187] It can be seen that the ZnO and Fe3O4 nanoparticles directly mixed in the same proportion do not have the synergistic effect between the active nanoparticles and the magnetic nanoparticles in the ZnO-Fe3O4 hollow nanoaggregate microsphere catalyst constructed by spray drying, and the catalytic efficiency cannot be improved. In addition, the ZnO nanoparticles cannot be recovered by an external magnetic field.
[0188] Comparative Example 3
[0189] In this comparative example, an aqueous CeO2 dispersion with an average particle size of 3 nm is used as a catalyst, and is used to degrade PET polyester in the same proportion as in Example 3, comprising the following steps:
[0190] (1) 10 g PET powder, 60 g ethylene glycol solvent, and 0.1 g CeO2 catalyst were added into a parallel high-pressure reactor and reacted at 180 °C, 40 min, and 500 r / min magnetic stirring;
[0191] (2) After the system is cooled, the monomer product is obtained by dissolving and filtering.
[0192] After the reaction, the degradation rate of PET was measured to be 70.5%, and the yield of monomer product was 65.4%, which was about 5% lower than that of hollow nano aggregate microspheres.
[0193] It can be seen that when CeO2 nanoparticles are directly used for polyester degradation, the efficiency is lower than that of active CeO2 hollow nanoaggregate microspheres constructed by spray drying. At the same time, the ultra-small CeO2 nanoparticles dispersed in the reaction system cannot be completely separated from the product (ethylene terephthalate crystals), while the micron-sized CeO2 hollow nanoaggregate microspheres can be separated by centrifugation or filtration while the product crystals are dissolved.
[0194] Comparative Example 4
[0195] This comparative example uses an aqueous ZnO dispersion with an average particle size of 6 nm as a catalyst, and uses it in the same proportion as in Example 4 to degrade PET polyester, comprising the following steps:
[0196] (1) 10 g PET powder, 60 g ethylene glycol solvent, and 0.1 g ZnO catalyst were added into a parallel high-pressure reactor and reacted at 180 ° C, 40 min, and 500 r / min magnetic stirring;
[0197] (2) After the system is cooled, the monomer product is obtained by dissolving and filtering.
[0198] After the reaction, the degradation rate of PET was measured to be 75.9%, and the yield of monomer product was 72.9%, which was about 6% lower than that of hollow nano-aggregate microspheres.
[0199] It can be seen that when ZnO nanoparticles are directly used for polyester degradation, the efficiency is slightly lower than that of active ZnO hollow nanoaggregate microspheres constructed by spray drying. At the same time, the ultra-small ZnO nanoparticles dispersed in the reaction system cannot be completely separated from the product (ethylene terephthalate crystals), while the micron-sized ZnO hollow nanoaggregate microspheres can be separated by centrifugation or filtration while the product crystals are dissolved.
[0200] Obviously, the above embodiments of the present invention are merely examples for clearly explaining the present invention, and are not intended to limit the implementation methods of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all implementation methods here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.
Claims
1. A composite magnetic hollow nano aggregate microsphere catalyst for degrading polyester, characterized in that: The surface of the catalyst is composed of active nanoparticles and magnetic nanoparticles, and the interior is a hollow structure; the magnetic nanoparticles and active nanoparticles are dispersed in a solvent to form a mixed dispersion or suspension, and then combined into a composite magnetic hollow nano aggregate microsphere catalyst by spray drying; the particle size of the active nanoparticles is 2-100 nm; the particle size of the composite magnetic hollow nano aggregate microsphere is 1-30 μm; The active nanoparticles are selected from one or two of CeO2 and ZnO; The magnetic nanoparticles are selected from one or more of γ-Fe2O3, Fe3O4, FeO, FeCo, CoFe2O4, ZnFe2O4, NiFe2O4, MnFe2O4, Co3O4, Mn3O4, FeN, and Fe2N.
2. The method for preparing the composite magnetic hollow nano aggregate microsphere catalyst for degrading polyester as claimed in claim 1, characterized in that: The steps include: S21, dispersing the active nanoparticles and the magnetic nanoparticles in a solvent, and mixing them uniformly to obtain a mixed dispersion or suspension; S22, pumping the mixed dispersion or suspension into a spray dryer for spray drying to obtain a composite magnetic hollow nano aggregate microsphere catalyst.
3. The method for preparing the composite magnetic hollow nano aggregate microsphere catalyst according to claim 2, characterized in that: In step S21, the mass ratio of the active nanoparticles to the magnetic nanoparticles is 0.1-10:
1.
4. The method for preparing the composite magnetic hollow nano aggregate microsphere catalyst according to claim 2, characterized in that: In step S21, the solvent is selected from one or more of water, methanol, ethanol, ethylene glycol, cyclohexane, tetrahydrofuran, toluene, acetone, and N,N'-diethylformamide.
5. The method for preparing the composite magnetic hollow nano aggregate microsphere catalyst according to claim 2, characterized in that: In step S21, the solid content of the mixed dispersion or suspension is 0.1-10%.
6. The method for preparing the composite magnetic hollow nano aggregate microsphere catalyst according to claim 2, characterized in that: In step S22, the inlet temperature of the spray drying is 90-180°C.
7. The method for preparing the composite magnetic hollow nano aggregate microsphere catalyst according to claim 2, characterized in that: In step S22, the input rate of the mixed dispersion or suspension is 0.1-2 L / h.
8. The method for preparing the composite magnetic hollow nano aggregate microsphere catalyst according to claim 2, characterized in that: In step S22, the compressed air velocity during spray drying is 400-800 L / h.
9. An application of the composite magnetic hollow nano aggregate microsphere catalyst as claimed in claim 1 in the recycling of degraded polyester, characterized in that: The steps include: S41, adding polyester fragments, alcoholysis agent and composite magnetic hollow nano aggregate microsphere catalyst into a reaction kettle, stirring at a reaction temperature, so that the polyester undergoes a catalytic degradation reaction; S42, while hot, separate the composite magnetic hollow nano aggregate microsphere catalyst by using an external magnetic field, and after the system is cooled, obtain a purified product by dissolving and filtering; In step S41, the polyester fragments are one or more of polyethylene terephthalate, polybutylene terephthalate, polycarbonate, polycaprolactone, polylactide, and polyurethane; In step S41, the alcoholysis agent is one or more of methanol, ethanol, ethylene glycol, diethylene glycol, isooctyl alcohol, propylene glycol, butanediol, hexanediol, and sec-butanol; In step S41, the mass ratio of the polyester fragments, the alcoholysis agent and the composite magnetic hollow nano-aggregate microsphere catalyst is 1:3-20:0.005-0.05; In step S41, the reaction temperature is 160-210°C and the reaction time is 10-120 min; In step S41, the stirring rate is 100-1000 r / min.
Citation Information
Patent Citations
Ultrasonic / magnetic resonance bimodal contrast agent and its preparation method and use
CN104399091A
Method for degrading waste polyester based on magnetic recyclable nano-catalyst
CN115340706A